Two DRB3 residues predictively associate with the progression to type 1 diabetes among DR3 carriers - Zhao, Lue Ping; Papadopoulos, George K; Skyler, Jay S; Kwok, William W; Bondinas, George P; Moustakas, Antonis K; Wang, Ruihan; Pyo, Chul-Woo; Nelson, Wyatt C; Geraghty, Daniel E; Lernmark, Åke ; 0000-0003-1735-0499 (JCI Insight, 2025)
HLA-DR genes are associated with the progression from stage 1 and stage 2 to onset of stage 3 type 1 diabetes (T1D), after accounting HLA-DQ genes with which they are in high linkage-disequilibrium. Based on an integrated cohort of participants from two completed clinical trials, this investigation finds that sharing a haplotype with the DRB1*03:01 (DR3) allele, DRB3*01:01:02 and *02:02:01 have respectively negative and positive associations with the progression. Further, we uncovered two residues (β11, β26, participating in pockets 6 and 4, respectively) on the DRB3 molecule responsible for the progression among DR3 carriers, i.e. motif RY and LF respectively delay and promote the progression (Hazard Ratio = 0.73 and 2.38, p-value = 0.039 and 0.017, respectively). Two anchoring pockets 6 and 4 probably bind differential autoantigenic epitopes. We further investigated the progression association with the motifs RY and LF among carriers of DR3 and found that carriers of the motif LF have significantly faster progression than carriers of RY (HR = 1.48 and p = 0.019 in unadjusted analysis; HR = 1.39, p = 0.047 in adjusted analysis). New insights provide an impetus to examine the possible role of specific DRB3-binding peptides in the progression to T1D.